2017
DOI: 10.3390/medsci5020011
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Bacteriuria: A Longitudinal Study among Stroke Outpatients and Inpatients at the Korle-Bu Teaching Hospital in Ghana

Abstract: Infections of the urinary tract constitute an important post-stroke complication but in Africa, little is known about such infections in relation to stroke patients. The aim of the study was to investigate the epidemiology of bacteriuria among stroke patients at the Korle-Bu Teaching Hospital (KBTH) in Ghana including the prevalence, incidence, risk factors and aetiological agents. This was a longitudinal study involving 55 outpatients and 16 inpatients of stroke from the physiotherapy clinic and stroke admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…In this study, the uropathogenic distribution was consistent with study by Donkor et al [23] but differed from that of study The statistical analysis was performed using multinomial logistic regression analysis. CRE = carbapenem-resistant Enterobacteriaceae, VRE = vancomycin-resistant enterococcus.…”
Section: Discussionsupporting
confidence: 74%
“…In this study, the uropathogenic distribution was consistent with study by Donkor et al [23] but differed from that of study The statistical analysis was performed using multinomial logistic regression analysis. CRE = carbapenem-resistant Enterobacteriaceae, VRE = vancomycin-resistant enterococcus.…”
Section: Discussionsupporting
confidence: 74%
“…It is important to note that the data included in this systematic review was largely from the developed world and there was hardly any data from Sub-Saharan Africa. In Ghana, a recent study reported a significantly higher prevalence of UTI among stroke outpatients (24.3%) than among a healthy control group (7.2%) [91], while another study reported a significantly higher prevalence among stroke inpatients (18.8%) than among outpatients (10.9%) [92]. Risk factors of UTI among stroke patients include stroke severity, depressed conscious level, increased post-void residual urine volume, catheterization, and diabetes mellitus [90].…”
Section: Stroke and Infectionsmentioning
confidence: 99%
“…A number of bacterial pathogens have been implicated in UTI among stroke patients and the major ones include Staphylococcus aureus and gram-negative bacteria such as Pseudomonas aeruginosa , Escherichia coli , and Enterobacter spp. [9092]. Compared to UTI, pneumonia is a more serious complication following stroke and is commonly caused by Klebsiella pneumoniae , Pseudomonas aeruginosa , and Escherichia coli [90, 93].…”
Section: Stroke and Infectionsmentioning
confidence: 99%
“…In Ghana, a recent study by Codjoe [ 192 ] showed that KPC was absent in all 111 carbapenem resistant Gram-negative bacteria that were screened; the carbapenemase genes identified were bla NDM-1 in Acinetobacter baumannii , bla VIM-1 in Pseudomonas species and bla OXA-48 in Klebsiella pneumoniae . In Ghana, multi-drug resistance of Gram-negative bacteria has reached alarming rates [ 193 , 194 , 195 , 196 ]. Strict infection control measures and regular surveillance programmes instituted by countries such as Australia and New Zealand have recorded prevalence as low as 1% of KPC harbouring genes in hospital acquired Enterobacteriaceae infections.…”
Section: Epidemiology Of Carbapenemase-producing Organismsmentioning
confidence: 99%